Shape-stabilized composite phase change materials with high thermal conductivity based on stearic acid and modified expanded vermiculite. (November 2017) - Zhang, Xiaoguang; Yin, Zhaoyu; Meng, Dezhi; Huang, Zhaohui; Wen, Ruilong; Huang, Yaoting; Min, Xin; Liu, Yangai; Fang, Minghao; Wu, Xiaowen
Abstract: Stearic acid (SA) and modified expanded vermiculite (EV) shape-stabilized composite phase change materials (ss-CPCMs) with enhanced thermal conductivity were prepared. EV was impregnated with a starch solution, and then a composite of EV and carbon (EVC) was obtained by carbonizing starch in-situ in the EV layers. 63.12 wt % of SA was retained in the SA/EVC ss-CPCMs without leakage. Scanning electron microscopy (SEM) images showed that the EVC with highly porous micro-pores acted as a good support matrix for absorbing molten SA. The thermal conductivity of the SA/EVC ss-CPCMs was 0.52 W/(m K), and this was an increase of 52.9% compared with that of the SA/EV ss-CPCMs. The results from Fourier transform infrared spectroscopy (FT-IR), Differential scanning calorimeter (DSC), thermogravimetric analysis (TGA), and thermal cycling tests indicated that the prepared SA/EVC ss-CPCMs are a promising material for energy efficient buildings because of their optimum phase-change temperature, a high enthalpy of phase change, ideal thermal conductivity, and good chemical and thermal stability. Highlights: The expanded vermiculite/carbon (EVC) was prepared by in-situ starch carbonization. The EVC was a satisfactory SA supporting matrix. The thermal conductivity of the SA/EVC ss-CPCMs was 0.52 W/(m K). The SA/EVC ss-CPCMs has high enthalpy of phase change, and good thermal stabilities.